Puberdade precoce central em crianças atendidas em serviço especializado de Fortaleza : características epidemiológicas e perspectivas em saúde pública - Cavalcante, Celso Junior Wanderley (2012)
Introduction: Precocious puberty (PP) is an increasingly common problem worldwide. PP children are at risk of early sexual initiation, sexual abuse, short stature in adult life, increased risk of obesity, hyperinsulinemia and hypertension. The study addresses the frequency and conditions associated with PP in order to propose measures to reduce this public health problem and its possible sequels. Methods: A cross-sectional study develops analytical approach to children affected by PP, who were given assistance at the clinic of Endocrinology, in the University Hospital Walter Cantídio (HUWC) in the period from 1994 to 2010, with a sample of 342 children aged 1 to 11 years. The variables looked over included the biological, socio-economic, family and nutrition features. Data analysis was performed by using the SPSS program by means of the chi-square test to evaluate any association with the alpha value of 5%. Results: A ratio female-male of 37:1 was found. The most frequent features of children with PP were: dark skin, 64.1%; adopted, 7.3%; overweight and obesity, 27.1 and 25.1%, respectively; onset of puberty under 5 years, 27.1%; parental height below the average population, 80%. Children with late PP assistance by specialized service tended to show early signs of puberty (p <0.001) and belong to households with lower income (p <0.002). Conclusions: It was found a high proportion of children with PP which had been adopted and that had overweight/obesity, two important risk factors in the genesis of the problem. The delay in specialized care was associated with signs of very early onset of puberty and low household income, which suggests that public health actions are required to encourage detection and attention to the problem among the poorest strata of the population.